Effect of Cowpea and Pumpkin Powders on the Physicofunctional Properties, Total Phenolic Content, Antioxidant Activity, and Consumer Acceptability of Soup - Nyarai Mungofa; Daniso Beswa (International Journal of Food Science)
Cowpea (Vigna unguiculata) and pumpkin (Cucurbita maxima) play a pivotal role as affordable, nutritious food sources for humans. Low-income households can significantly benefit from supplementing their diet with nutritious and cost-effective locally available ingredients. The aim of this research was to develop a cost-effective soup formulation using ingredients that are readily available from a household garden and suitable for use in the kitchens of families with limited financial resources. The effect of cowpea and pumpkin powders on physicofunctional properties, total phenolic content (TPC), antioxidant activity (AA), and consumer acceptability of the soup were determined. Three composite soup mixes were prepared using various parts of cowpea and pumpkin at a ratio of 1:1. A control soup sample was developed, and the experimental soups were prepared by supplementing the control soup with 5%, 10%, or 15% of each composite soup mix, respectively. The physical properties, functional properties, TPC, AA, and consumer acceptability of soup were determined. The control soup had an appealing golden brown colour. Formulations 1 and 3 showed the highest relative viscosity (80.67–88.91 cP). All the experimental soup formulations had higher rehydration ratios (8–14.7 g/g) and water absorption capacities of 185.7–263.3 g/g compared to the control at 7.7 g/g and 65.7 g/g, respectively. The TPC of Formulation 2 (F2) (0.32–0.54 mg of gallic acid equivalent (GAE)/100 g powder) and Formulation 3 (F3) (0.54–0.63 mg GAE/100 g powder) was higher than Formulation 1 (F1) (0.25–0.32 mg GAE/100 g powder) and the control (0.44 mg GAE/100 g powder). Overall, the cowpea seed powder plus pumpkin fruit powder added at 10% in F2 appeared nearly optimal as a soup mix. It produced an attractive golden brown soup with increased swelling power (SP) and viscosity to assist in swallowing. Soup F1 and F2 scored high in appearance (7.27 and 7.0), aroma (7.1 and 6.7), taste (6.6 and 6.3), and overall acceptability (6.5 and 6.4). Despite having TPC and AA lower compared to F3, F2 containing 15% cowpea seed powder and pumpkin fruit has the potential to be further developed and commercialised due to the relatively high overall consumer acceptability and high acceptability in all sensory attributes.